Efecto de la instrucción con patrones lingüísticos en el aprendizaje léxico: el campo semántico “shine” - Sánchez, María Jesús (Estudios Ingleses de la Universidad Complutense, 2002)
The purpose of this research was to test the effect of formal instruction on the learning of English as a foreign language in the semantic field Shine. A Pretest- Posttest design with two dependent varibles (similarity and a lexical test) was used to test the structural change produced in the subjects who took part in this experiment. The number of subjects in this research was 150: 120 students of English as a foreignlanguage and 30 English native speakers. The results were successful in only one dependent variable (the lexical test), which indicate that instruction should be given bearing in mind different factors such as expert patterns.